O EQ-5D como medida de saúde para a população brasileira - Renata de Miranda Menezes (2014)
Measures of health-related quality of life have become widely used in economic evaluations because they incorporate social preferences on the analyses. The mostly applied preference-based instruments are EQ-5D, SF-6D and HUI. Health index scores for the Brazilian population were estimated using EQ-5D, from a survey that took place at Cedeplar / UFMG between 2010 and 2012. However, the results often differ depending on the choice of preference-based instruments used to provide utilities on these studies. Given the importance of the instrument chosen, this dissertation aims to analyze to what extent the EQ-5D describes health, comparing this instrument with traditional health measures, socioeconomic variables and the SF-6D. The methodology were based in descriptive analyzes, logistic regression and ordinary least squares (OLS) regression analyses. Moreover, a cluster analysis, named Grade of Membership (GoM), held to identify health profiles for the Brazilian population. Significant differences were found between population subgroups with respect to demographic, socioeconomic and health indicators. According to the health profiles, Brazilian population can be divided into four groups. The first profile represents extreme health limitations and individuals with lower socioeconomic status. The second and the third profiles identifies individuals with full health and higher socioeconomic status, which differ due to age-related characteristics. The fourth is an intermediate between the profile 1 and the profiles 2 and 3. On the other hand, the ceiling effect and the comparison with SF-6D shows that the EQ-5D descriptive system may not be capable of distinguishing between health states close to full health.